Reflections of Cultural Trauma in Romualdas Granauskas’s novel Duburys (The Pit) and Ramūnas Klimas’s Maskvos laikas (Moscow Time) - Mykolaitytė, Aurelija (Colloquia, 2017)
Cultural trauma is defined as the damage done to people’s lives when epochal breaks impact identity. Psychological, sociological, and literary research has shown that trauma discourse is still relevant today, that it is crucially important to talk about traumatic events related to Soviet-era experience. These two novels contribute to the powerful works exploring cultural trauma and attempting to grasp the scale of the damage it has effected. Romualdas Granauskas’s 2003 novel Duburys (The Pit) draws attention to the experiences of a Soviet individual who has left his rural origins: the struggle to adapt to city life, the loss of roots and lack of spiritual framework, the submission to fate. This is a passive Soviet-era person – someone lacking any sense of initiative or belonging, who leaves no sign of his existence. Granauskas depicts the complete erasure of this individual’s original identity and how his new one is marked by the conflict of hiding his true nature as he is overwhelmed by a new, foreign context. Another view of the Soviet era is revealed in Ramūnas Klimas’s 2005 novel Maskvos laikas (Moscow Time), which depicts the intellectual circles, the awakening of consciousness as opposed to oblivion; here the work of memory is focused on childhood events, in particular the humiliation of the protagonist’s father. The novel focuses a great deal on the state, and process, of being “under someone’s boot” and how this kind of degradation can be carried into adulthood. Although the novel does not depict overt resistance, it describes the character’s refusal to accept the condition of degradation; the Soviet occupation is understood as a period of degradation during which a coercive system caused deep psychic damage. The author of this article presents Klimas’s novel as the judgement upon the Soviet period inspired by the awakening consciuosness, a judgement in which the reader is invited to take part.